Risk factors for recurrent wheezing after infant bronchiolitis: a 6-year single-centre follow up study in China - Chen, Sainan; Xu, Xueyun; Wu, Min; Zhou, Luting; Wang, Yuqing (Frontiers in Pediatrics, 2025)
BackgroundInfants with bronchiolitis have an increased risk of developing recurrent wheezing and asthma. However, the risk factors for recurrent wheezing or asthma after infant bronchiolitis remain controversial. The aim of our prospective observational study was to seek the risk factors for recurrent wheezing or asthma.MethodsInfants with first bronchiolitis attack at the respiratory department, Children's Hospital of Soochow University were enrolled from November 2016 through March 2017. Serum cytokines, TSLP, IL2, IL13, TIMP-1, MMP-9, IL33, IL5, IL4, IL25, TNF-α and MIP-1α were measured via flow cytometry at enrolment. Patients were followed up with every 3 months for a duration of 6 years by telephone or as outpatients for the number of wheezing episodes. In the sixth year of follow-up, lung function tests, total IgE and allergen specific IgE test were performed in those children at 6–7 years of age.ResultsWe enrolled 89 infants, 72 of whom were successfully followed up for 6 years. In total, 31.9% of the patients developed recurrent wheezing and 12.5% of patients developed asthma after 6 years of follow-up. The Kaplan–Meier curves of the overall analytic cohort (n = 72) revealed that compared with those in the non-eczema group and non-RSV group, the rate of recurrent wheezing preschool was significantly higher in patients with bronchiolitis with eczema and RSV (P < 0.05). There were no significant differences in cytokine levels between patients with and without current asthma (P > 0.05).ConclusionsA total of 31.9% of the children with hospitalization for bronchiolitis at an early age developed recurrent wheezing and 12.5% developed asthma at 6-years old. Infants hospitalised with RSV bronchiolitis and/ or with a history of eczema were at increased risk for developing recurrent wheezing.